Ben Sira’s Idea on the Role and Tasks of the Physician in the Process of Healing the Sick (Sir 38:12–15) - Piwowar, Andrzej (The Biblical Annals, 2024)
The last part of Ben Sira’s reflections on the activities of his contemporary physicians and the medicine of the time contained in Sir 38:1–15 is devoted to the attitude of the medical practitioner when healing the sick person (38:12–15). The pericope has a concentric structure with the attitude of the physicians towards God at its centre (38:13–14). The frame verses are devoted to the attitude of the sick person (38:12) and the sinner (38:15) towards the physician. According to the sage, it is not enough for a suffering person to turn to God alone asking to restore their health (Sir 38:9–11), but they should call on a doctor to help them recover (38:12a). The sick person needs a doctor’s help (38:12b). The Greek text emphasises that one should not be afraid of a doctor because God created them (the Hebrew version omits this argument; see 38:12a). Therefore, physicians are desired by the Lord and, like all creatures, God has also assigned them a specific task. However, physicians cannot rely solely on their knowledge and skills while healing a sick person. They should ask (pray to) God to allow them first to make the correct diagnosis (as explicitly stated in the Hebrew version), and then to heal their patient. The last verse of the pericope (38:15) poses many difficulties, which are reflected in numerous interpretations of its content. According to the analysis made in the article, it does not contain a negative image of a medical practitioner because its main message is the link between the cause of illness and sin (traditional perception of illness expressed in the Old Testament based on the principle of retribution). In Sir 38:12–15, as well as in the entire reflection on the contemporary medicine (38:1–15), Ben Sira made an excellent synthesis between this field of science and Israel’s faith in the divine Physician.